Mitigating Seasonality in Uzbekistan's Tourism Sector: Impacts and Countermeasures - Kilichova Orzigul; Murodullayev Bekzod; Norkulova Dilfuza (Indonesian Journal of Cultural and Community Development, 2023)
This research undertakes a comprehensive examination of seasonality in Uzbekistan's tourism services market, with the ultimate goal of devising strategies to mitigate its adverse effects. Utilizing methods such as logical reasoning, deductive analysis, and statistical as well as economic analyses, the study explores various factors influencing seasonality in tourism. These factors include natural-climatic conditions, economic solvency, social timing, demographic demand, psychological elements, logistics development, and service quality. The analysis categorizes these variables into primary (natural-climatic) and secondary (all remaining) influences. Our results indicate that 94.9% of foreign tourists to Uzbekistan in the first quarter of 2022 were from CIS countries, reflecting a marked decrease in tourist arrivals, particularly from non-CIS countries, attributable to pandemic-induced flight restrictions and quarantine measures. This downturn underscores the urgency for strategic interventions to minimize seasonality's negative impact on Uzbekistan's tourism economy, thereby improving the country's tourism sector's resilience against external shocks. Highlights: Seasonality in tourism is driven by diverse factors, both primary and secondary. Pandemic-led measures triggered an 80.3% plunge in Uzbekistan's foreign tourist arrivals in Q1 2021. Strategic actions to minimize seasonality's impact can boost the resilience of Uzbekistan's tourism sector. Keywords: Seasonality, Uzbekistan, Tourism Sector, Mitigation Strategies, Pandemic Impact.